FROST INVESTIGATION 1944-1945. APPENDIX 11. REPORT ON SUBSURFACE TEMPERATURE INVESTIGATIONS AT PIERRE AIRFIELD, PIERRE, SOUTH DAKOTA, WATERTOWN AIRFIELD, WATERTOWN, SOUTH DAKOTA, FARGO MUNICIPAL AIRFIELD, FARGO, NORTH DAKOTA. APPENDIX 12. REPORT ON SUBSURFACE TEMPERATURE INVESTIGATIONS AT DOW FIELD, BANGOR, MAINE, PRESQUE ISLE AIRFIELD, PRESQUE ISLE, MAINE. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1945)
The purpose of the subsurface temperature investigations was the determination of the temperature changes occurring in and beneath airfield pavements during winter weather conditions, and a correlation of this data with air temperature and cumulative degree-days below freezing data obtained during the same period of time. Depth of freezing temperature penetration and data relative to heat movements through the surface and from deep earth were also obtained. (Author) See also Appendices 8-10, AD-712 390 and Appendix 13, AD-712 471.